Do fine feathers make a fine bird? The influence of attractiveness on fraud‐risk judgments by internal auditors. Issue 3 (26th September 2018) - Eulerich, Marc; Theis, Jochen C.; Lao, Junpeng; Ramon, Meike
Abstract : Independence and objectivity are key principles assumed to underlie internal auditors' fraud‐risk judgments. However, a substantial body of evidence suggests that physical attractiveness of suspects may influence internal auditors' fraud‐risk judgments. In this experimental study we investigated whether internal auditors are susceptible to appearance‐related biases, or whether they correct for them due to their expertise and motivation. A total of 193 internal auditors were presented a misappropriation‐of‐assets scenario in which the attractiveness of a suspect was manipulated. To determine whether professional expertise is associated with increased resilience to appearance‐related biases, their fraud‐risk judgments were contrasted with those acquired from 240 subjects without auditing experience ("naive subjects"). In line with our predictions, attractiveness modulated naive subjects' fraud‐risk judgments, whereas internal auditors did not show any indication for appearance‐related biases. Our findings suggest that internal auditors' experience and motivation may immunize them to the phenomena of physical attractiveness stereotyping and the attractiveness halo effect.